Unveiling EFL teacher’s voices on PKGBI professional development: A narrative inquiry - Rizal Wahid Permana Putra; Amaria Fajar Nurrakhma; Dwi Fita Heriyawati (Universitas Muhammadiyah Malang, 2025)
As education practices in 21st century has grown rapidly, it grows a wide agreement that English teachers must improve their practical and pedagogical skills through continuous professional development program. This study aimed to investigate EFL teachers’ voices towards PKGBI professional development program. Further, this study employed qualitative study with a narrative inquiry approach. This study employed semi-structured interviews and thematic analysis regarding teachers’ voices on PKGBI professional development. Based on the results of data analysis, the findings suggested that most EFL teachers showed positive voices and perceptions towards PKGBI program. PKGBI professional development program was said to be an effective program in improving EFL teachers’ pedagogical and professional competencies. This study also highlighted the challenges faced by the EFL teachers during the professional development program such as ICT integration, excessive workload as a teacher, and time management. This study underscores the importance professional development program for English teachers dealing with the rapid changes in educational issues in the next fifteen years ahead. To sum up, this study suggested that undertaking PKGBI professional development program has been an alternative-continuous professional development program for English teachers, and it has profoundly increased EFL teachers’ pedagogical and professional competencies in addressing to 21st century learning.